'Royal diplomacy: British preparations for the State Visit of King George VI and Queen Elizabeth to the United States, June 1939.'. Issue 2 (3rd April 2021) - Johnson, Gaynor
ABSTRACT: This article explores the preparation made by the British government, primarily the Foreign Office, for the state visit of King George VI and Queen Elizabeth to the United States three months before the outbreak of the Second World War. It considers the dynamics of the relationship between the officials in Whitehall, the British ambassador in Washington, Sir Ronald Lindsay, the agenda of the Roosevelt administration and the role of the British royal family as ambassadors in their own right. Lindsay's role was also pivotal because he was a personal friend of the King and was also on much respected and influential figure in Washington. The article does not discuss the course of the state visit, although there is discussion of the literature that relates to it. However, it does reveal that securing a concrete alliance with the United States was not the priority of the British government in the summer of 1939; that the focus of the Foreign Office, in particular, was on the growing diplomatic crisis in Europe. Lastly, the article argues that in the months leading up to the outbreak of the Second World War, the Foreign Office was confident in its own ability to lead the formulation of British foreign policy; that it was not eclipsed by Neville Chamberlain's very personal involvement in appeasing the fascist dictators.